Comparative Effects of Novel Modified Sleeper and Cross-body Stretching on Scapular Anterior Tilting and Shoulder Internal Rotation in Subjects With Anterior Tilted Scapular and Shoulder Internal Rotation Deficits - Yeonghun Han; Chung-hwi Yi; Woochol Joseph Choi; Oh-yun Kwon (Korean Research Society of Physical Therapy, 2023)
Background: Posterior capsule tightness (PCT), commonly seen in overhead athletes, is a soft tissue adaptation that is also noted in non-throwers. PCT is associated with scapular and humeral kinematic alterations, significant restriction of shoulder internal rotation (IR) range of motion (ROM), and significant scapular anterior tilting. Sleeper and cross-body stretches (CBS) are suggested for PCT and IR deficits, and have been modified since introduction. A novel modified sleeper stretch (NMSS) was designed in this study to prevent the risk of anterior translation of the humeral head. Though the effects of posterior shoulder stretching exercise have been widely studies, to the best of our knowledge, no previous studies have investigated the effectiveness of posterior shoulder exercises in decreasing scapular anterior tilting. Objects: To compare the immediate effects of two posterior shoulder stretching exercises (NMSS and CBS) on scapular anterior tilting and shoulder IR ROM. Methods: Thirty-two subjects with anteriorly tilted scapula and IR deficits [mean age: 24.3 ± 2.5 years; 15 males and 17 females] participated in this study. Subjects were randomly assigned to either the NMSS or CBS groups. Scapular anterior tilting (at rest and at shoulder 60° active IR) and shoulder IR ROM were measured before and immediately after intervention. Results: Scapular anterior tilting significantly decreased, while the shoulder IR ROM significantly increased in both groups. However, there was no significant group-by-time interaction effect or significant difference between the groups. Conclusion: Both stretching exercises were effective in restoring shoulder IR ROM and decreasing scapular anterior tilting.